1995
DOI: 10.1063/1.114689
|View full text |Cite
|
Sign up to set email alerts
|

Creation of nanostructures on gold surfaces in nonconducting liquid

Abstract: With the application of voltage pulses, mounds of 20 nm in diameter and 2 nm in height on the average can be created on a gold surface with very high efficiency in nonconducting liquid from a gold tip. The created mounds are similar to those produced in air. Tungsten and PtIr tips are also used in this study and the dominant shapes of created structures are craters and volcanolike mounds, respectively. Our data show that these nanometer structures are created by a mechanical contact between the tip and the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…This appearance of mounds and craters is also well known from nanostructuring experiments where contact was established [17] or voltage pulses were applied [18,19]. In some experiments it was already concluded that field emission is not the crucial process for the pattern formation [18][19][20].…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This appearance of mounds and craters is also well known from nanostructuring experiments where contact was established [17] or voltage pulses were applied [18,19]. In some experiments it was already concluded that field emission is not the crucial process for the pattern formation [18][19][20].…”
Section: Resultsmentioning
confidence: 71%
“…In some experiments it was already concluded that field emission is not the crucial process for the pattern formation [18][19][20]. Alternatively it was suggested that the extent of cohesion between tip and surface and a subsequent plastic deformation is the crucial parameter of the pattern formation [17,19].…”
Section: Resultsmentioning
confidence: 99%
“…4(b). The point contact or field evaporation is not a plausible mechanism for a mound formation because the formation of the craters or pits are not observed as such in typical Au surfaces with hard tungsten tips [11]. Also, the current is not as large as in point contact during the fabrication.…”
Section: µMmentioning
confidence: 99%
“…Further, we determine the conditions under which this purely elastic deformation results in jump to contact and show that they agree quantitatively with published experimental results by Guo and Thompson [11] for material transfer between tip and sample by voltage pulsing. Field-induced elastic jump to contact is thus an alternative to the field evaporation mechanism proposed in many STM nanofabrication experiments [11][12][13] the validity of which remains controversial [11,14].…”
Section: Field-induced Deformation As a Mechanism For Scanning Tunnelmentioning
confidence: 99%
“…This discrepancy may occur in part because large-scale elastic deformation is precluded in molecular dynamics simulations, due to the small volume in which atomic coordinates are allowed to relax. Indeed, if jump to contact can be achieved by purely elastic deformation, then this will preempt mechanisms that have been proposed based on plastic deformation [11,14,26].…”
Section: Field-induced Deformation As a Mechanism For Scanning Tunnelmentioning
confidence: 99%